2009
DOI: 10.1093/beheco/arp150
|View full text |Cite
|
Sign up to set email alerts
|

Small folivorous primate groups exhibit behavioral and physiological effects of food scarcity

Abstract: The influence of diet and food distribution on the socioecology of group-living species has long been debated, particularly for primates. It has typically been assumed that folivorous primates experience relatively little feeding competition due to the abundant, widespread nature of their food, freeing them to form large groups in response to predation, to disperse with relative ease, and to have egalitarian female social relationships. Recent studies, however, have come to different conclusions about the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 62 publications
2
63
0
Order By: Relevance
“…In some previous studies it has been reported that, although folivorous primates have a higher chance of diet selection because of resource abundance, they are selective by nature and use very few resources for overall consumption [Harris et al, 2009]. Although lion-tailed macaques were not observed to consume leaves, bonnet macaques occasionally consumed leaves, mainly young and whole-leaf flush or their petioles.…”
Section: Discussionmentioning
confidence: 91%
“…In some previous studies it has been reported that, although folivorous primates have a higher chance of diet selection because of resource abundance, they are selective by nature and use very few resources for overall consumption [Harris et al, 2009]. Although lion-tailed macaques were not observed to consume leaves, bonnet macaques occasionally consumed leaves, mainly young and whole-leaf flush or their petioles.…”
Section: Discussionmentioning
confidence: 91%
“…Briefly, C-peptide is a byproduct of the production of insulin, one of the key hormones regulating intermediary metabolism and a key chemical signal and regulator of energy balance [Rubenstein et al, 1969;Schwartz et al, 1992;Strack et al, 1995;Norman & Litwack, 1997]. C-peptide, therefore, offers a noninvasive way to track changes in energetic condition in wild primates and has been validated against measures of weight loss/gain [Valeggia & Ellison, 2004;Deschner et al, 2008;Girard-Buttoz et al, 2011], dietary quality Harris et al, 2010;Georgiev et al, 2011], food availability [Emery Thompson & Knott, 2008], estimated caloric intake [Emery Thompson & Knott, 2008], and activity levels in a variety of primate species. C-peptide is valuable for monitoring the costs of lactation not only because it provides a general biomarker for energy balance but also because changes in insulin production and sensitivity are essential for the metabolic shifts that divert maternal energy toward milk production [Flint et al, 1979;Jones et al, 1984;Vernon, 1989;Tigas et al, 2002].…”
Section: Energetics and Lactationmentioning
confidence: 99%
“…Deficiency in macronutrients can also be shown by urinalysis that quantify ketone and c-peptide concentrations as indices of energy balance (Harris et al 2009;Harrison et al 2010;MacIntosh et al 2012) and urea and d…”
Section: Studies On Resource Limitation At the Behavioral Levelmentioning
confidence: 99%